ASSESSMENT OF PSYCHO-SOCIAL IMPACT OF ACNE AMONG YOUNG ADULTS - A CROSS SECTIONAL STUDY AT A TERTIARY CARE HOSPITAL OF RAWALPINDI - Rashid, Zubaida; Mashhadi, Syed Fawad; Sharif, Imtenan; Zaidi, Syeda Urooj; Maroof, Saira; Khan, Mufliha; Liaqat, Umama (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the psychosocial impact of acne and to evaluate the quality of life in relation to severity of symptoms among young adults.Study Design: Cross-sectional – analytical study.Place and Duration of Study: Outpatient Department, Pak Emirates Military Hospital, Rawalpindi, from Sep 2018 to Feb 2019.Methodology: We included 300 individuals visiting the hospital and their quality of life was assessed using Acne quality of life Index questionnaire. Data was analyzed using SPSS-23.Results: Total scores were calculated for three domains of Quality of life in patients with Acne i.e. Self-perception, Emotional well-being and Social life. Out of these three domains, Social Life was most affected by acne (mean score 15.61 ± 7.37out of a total of 30) and Self-Perception was seen to be least affected (mean score 16.90 ± 8.20). There was a strong positive co-relation between the increasing severity of symptoms and impact on Self Perception (r=-0.58, p